KEPUASAN WISATAWAN MUSLIM: ANALISIS PULL MOTIVATION DAN ISLAMIC ATTRIBUTES DI KABUPATEN GARUT - Syska Septiani, - (2020)
In the marketing literature, satisfaction is considered a key concept that guides marketers, customers and consumers. Departing from this, this research is based on the problem that there are gaps in the target and realization of tourists wisiting Garut, and there are Google reviews, the lowest reviews of tourists are less satisfied with tourist facilities in Garut. This study aims to analyze the effect of the level of pull motivation and Islamic attributes on the level of satisfaction of Muslim tourists in Garut Regency. The research method used is quantitative with causality research design. The analysis tool used is Partial Least Square-Structural Equation Modeling (PLS-SEM). The subjects of this study were Muslim tourists who had traveled to Garut with a total sample of 200 respondents.The result show that the level of pull motivation, Islamic attributes and satisfaction of muslim tourist has a high category. Then hyphothetical test the variable level of pull motivation and the level of Islamic attributes significantly positive effect on the level of satisfaction of Muslim tourists. The results of this study are expected to be useful for the development of tourism in Garut and can be input for stakeholders, especially travel agents and tourism agencies in the region of Garut.